Random measurement and prediction errors limit the practical relevance of two velocity sensors to estimate the 1RM back squat - Warneke, K.; Skratek, J.; Wagner, C.-M.; Wirth, K.; Keiner, M. (Frontiers in Physiology, 2024)
Introduction: While maximum strength diagnostics are applied in several sports and rehabilitative settings, dynamic strength capacity has been determined via the one-repetition maximum (1RM) testing for decades. Because the literature concerned several limitations, such as injury risk and limited practical applicability in large populations (e.g., athletic training groups), the strength prediction via the velocity profile has received increasing attention recently. Referring to relative reliability coefficients and inappropriate interpretation of agreement statistics, several previous recommendations neglected systematic and random measurement bias.